NEFROLITÍASE BILATERAL EM FÊMEA CANINA: RELATO DE CASO - Rick, Gabriel Woermann; Da Cruz, Fernando Silvério Ferreira; Serafini, Gabriele Maria Callegaro; Da Rosa, Maurício Borges; Lukarewski, Rafael; Franke, Maira Cristiani (Salão do Conhecimento, 2018)
Relato de caso acompanhado durante estágio no Hospital Veterinário – UNIJUÍ;